2018
DOI: 10.1002/ep.13090
|View full text |Cite
|
Sign up to set email alerts
|

Performance of surfactant‐modified activated carbon prepared from dates wastes for nitrate removal from aqueous solutions

Abstract: New material (AC‐CTABr) was successfully prepared from chemical activation of dates wastes (AC), followed by cationic surfactant modification and was used to enhance nitrate removal from aqueous solutions. Brunauer, Emmett and Teller (BET) analysis revealed good binding of quaternary ammonium groups on the surface (1407 m2/g for the AC and 569 m2/g for the AC‐CTABr). Batch experiments were conducted to examine the effect of contact time, solution pH, adsorbent dose, and initial concentration of nitrate. Prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Similarly, Allalou et al [28] recorded an increase in the specific nitrate uptake from 32 to 80 mg/g but decrease in percentage anion removed from 92% to 40% as the initial concentration increased from 100 to 600 mg/L. For a fixed mass of adsorbent, at low initial adsorbate concentration, active binding sites are under saturated but tend towards saturation as the initial concentration increases [28]. This will make the ratio of adsorbed concentration to initial concentration decreases as the initial adsorbate concentration increases [16].…”
Section: Initial Concentration Percentage Inorganic Contaminants Remomentioning
confidence: 87%
See 4 more Smart Citations
“…Similarly, Allalou et al [28] recorded an increase in the specific nitrate uptake from 32 to 80 mg/g but decrease in percentage anion removed from 92% to 40% as the initial concentration increased from 100 to 600 mg/L. For a fixed mass of adsorbent, at low initial adsorbate concentration, active binding sites are under saturated but tend towards saturation as the initial concentration increases [28]. This will make the ratio of adsorbed concentration to initial concentration decreases as the initial adsorbate concentration increases [16].…”
Section: Initial Concentration Percentage Inorganic Contaminants Remomentioning
confidence: 87%
“…For instance, Kakavandi et al [26] observed that at pH 7, 1.2 g/L adsorbent concentration, 20˚C, 200 rpm, Co (II) specific uptake by SDS modified activated carbon increased from 16.4 to 40.8 mg/g while the percentage cation removed decreased from 98.2% to 49% as the initial Co (II) concentration increased from 20 to 100 mg/L. Similarly, Allalou et al [28] recorded an increase in the specific nitrate uptake from 32 to 80 mg/g but decrease in percentage anion removed from 92% to 40% as the initial concentration increased from 100 to 600 mg/L. For a fixed mass of adsorbent, at low initial adsorbate concentration, active binding sites are under saturated but tend towards saturation as the initial concentration increases [28].…”
Section: Initial Concentration Percentage Inorganic Contaminants Remomentioning
confidence: 95%
See 3 more Smart Citations